2021
DOI: 10.1111/febs.16129
|View full text |Cite
|
Sign up to set email alerts
|

UBQLN proteins in health and disease with a focus on UBQLN2 in ALS/FTD

Abstract: Ubiquilin (UBQLN) proteins are a dynamic and versatile family of proteins found in all eukaryotes that function in the regulation of proteostasis. Besides their canonical function as shuttle factors in delivering misfolded proteins to the proteasome and autophagy systems for degradation, there is emerging evidence that UBQLN proteins play broader roles in proteostasis. New information suggests the proteins function as chaperones in protein folding, protecting proteins prior to membrane insertion, and as guardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 190 publications
0
17
0
Order By: Relevance
“…In contrast, K63‐ and M1‐linked polyUb are typically involved in nonproteolytic signaling pathways such as cargo sorting, DNA repair, NF‐Kβ signaling, and autophagy (Olzmann et al , 2007 ; Haglund & Dikic, 2012 ; Linares et al , 2013 ; Piper et al , 2014 ; Sun et al , 2018 ). UBQLN2 has known affiliations with the proteasome, autophagy receptors (LC3) and cargo sorting adaptor proteins (epsin 1 and 2) (Zheng et al , 2020 ; Lin et al , 2021 ). We showed that UBQLN2 LLPS can be rapidly modulated by changes in cellular signaling (e.g., formation of K63‐linked chains or ubiquitinated substrates, Fig 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, K63‐ and M1‐linked polyUb are typically involved in nonproteolytic signaling pathways such as cargo sorting, DNA repair, NF‐Kβ signaling, and autophagy (Olzmann et al , 2007 ; Haglund & Dikic, 2012 ; Linares et al , 2013 ; Piper et al , 2014 ; Sun et al , 2018 ). UBQLN2 has known affiliations with the proteasome, autophagy receptors (LC3) and cargo sorting adaptor proteins (epsin 1 and 2) (Zheng et al , 2020 ; Lin et al , 2021 ). We showed that UBQLN2 LLPS can be rapidly modulated by changes in cellular signaling (e.g., formation of K63‐linked chains or ubiquitinated substrates, Fig 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, K63- and M1-linked polyUb are typically involved in non-proteolytic signaling pathways such as cargo sorting, DNA repair, NF-Kβ signaling, and autophagy (Haglund and Dikic, 2012; Linares et al, 2013; Olzmann et al, 2007; Piper et al, 2014; Sun et al, 2018). UBQLN2 has known affiliations with the proteasome, autophagy receptors (LC3) and cargo sorting adaptor proteins (epsin 1 and 2) (Lin et al, 2021; Zheng et al, 2020). We showed that UBQLN2 LLPS can be rapidly modulated by changes in cellular signaling (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquilin-2 (UBQLN2) is one of the four members of the ubiquilin (UBQLN) family in the human genome encoded by the U BQLN2 gene located on chromosome Xp11.21 (Kaye and Shows 2000 ). It is expressed in various tissues, but the highest expression levels are found in muscles and brain (Lin et al 2021 ). UBQLN2 localizes mainly in the cytoplasm where it functions in the maintenance of proteostasis.…”
Section: Autophagic Genes Involved In Alsmentioning
confidence: 99%